The Power Exercise Model of Kick Based on Digital Samsak in Taekwondo - Deden Budi Rosman; Iman Sulaiman; Fahmi Fachrezzy; Ibraheem Musa Oluwatoyin (Sriwijaya University Learning and Education International Journal, 2024)
This study is about creating and testing a digital bag-based training model to improve kick power in taekwondo. The research follows a development and testing approach based on the Borg and Gall 10-stage model. The training uses a digital bag as part of the equipment, and data analysis is done using a quasi-experimental design. The participants were 70 athletes aged between 12 and 16, divided into two groups: a control group with 35 people and an experimental group with 35 people. The results showed that the Independent Samples Test had a significance value of 0. 000, which is less than 0. 05. This means the digital bag-based training model has a significant effect on improving kick power. When testing how effective the model was in practice, the N-Gain score showed that the control group had an average score of 2. 6%, which is not very effective, while the experimental group had a score of 67. 8%, which is quite effective. The study also created a product with 45 training items based on the digital bag model. These 45 items were reviewed by three experts: a coach, a taekwondo trainer, and another taekwondo trainer. The conclusion is that the digital bag-based training model for kick power in taekwondo is both significant and effective in increasing kick power, and it results in 45 training items for use in taekwondo.